Comparing labour and total factor productivity growth and level in France, Japan, the United Kingdom and the United States over the past century and in recent years - Gilbert Cette; Yusuf Kocoglu; Jacques Mairesse (The Open Economics Journal, 2009)
The present study contributes to the analysis of economic growth by comparing labour ant total factor productivity (TFP) in France, Japan, the United Kingdom and the United States in the very long run (since 1890) and in the medium run (since 1980). During the past century, the United States has overtaken the United Kingdom and became the leading world economy. During the last 25 years, productivity growth has also known contrasted developments in the four countries, in particular as a result of an unequal growth of information and communication technology (ICT) investments. The past 120 years have been characterised by: (i) rapid economic growth and large productivity gains in the four countries; (ii) a decline in productivity in the United Kingdom relative to the United States, and to a lesser extent also relative to France and Japan until the second world war (WW2), and its subsequent come-back; (iii) the remarkable catching-up of the United States by France and Japan after WW2, which was however interrupted in the case of Japan during the 1990s. The contribution of capital deepening as it can be measured- accounts for a large share of these different performances, with an increasing share of ICT capital in the last 25 years. This contribution varies considerably over time and across the four countries, and it is always less important, except in Japan, than that of the unmeasured factors underlying TFP, such as labour skills, technical and organisational changes and knowledge spillovers. Most recently (in 2006), before the current world crisis, hourly labour productivity levels are slightly higher in France than in the United States, and significantly lower in the United Kingdom (by roughly 10%) and even more in Japan (30%), while TFP levels are very close in France, the United Kingdom and the United States, but much lower (40%) in Japan.
Keywords: O47; O57; E22; J24; N10; 330; productivity; growth accounting; macro-economic history